Balance Between Cost and Risk for Fund Manager When Adopting Diversification Method - Wang, Keqiang (2022)
Following the 2007-2008 financial crisis and acceleration of economic globalization, more market participants and regulators pay more attention to the role of portfolio diversification strategy in financial market. Various diversification strategies are applied by fund managers to reduce the idiosyncratic risk, including the Most Diversified Portfolio (MDP), Minimum Variance portfolio, Equally Weighted portfolio and Maximum Sharpe Ratio method. The paper describes how the diversification strategy improve the performance of investment portfolio and tries to find a optimal portfolio size for fund managers. A variety of quantitative methods are applied in the analysis including OLS regression, stationary test and Monte Carlo simulation with R. The analysis results have shown that there exists a trade-off between efficiency of diversification and downside risk of asset price. Furthermore, the optimal portfolio size is estimated using the Most Diversified Portfolio Method.